Analysis of Comorbidities in Breast Cancer Patients in the United Arab Emirates (UAE): Diabetes and Breast Cancer: A detailed examination - Shanbhag, Nandan Maruti; Al Ameri, Mouza; Alharmoodi, Fatima; Almheiri, Mariam; Alblooshi, Mohammed (International Journal of Innovative Research in Medical Science, 2024)
Introduction: This study focuses on the intricate relationship between diabetes and breast cancer in the United Arab Emirates (UAE). Both diseases are major health concerns globally, with diabetes potentially increasing the risk of several cancers, including breast cancer. The UAE has seen a rise in the prevalence of both conditions, influenced by genetic, environmental, and lifestyle factors. The primary aim of this research is to investigate the association between diabetes and the stage of breast cancer among patients in the UAE. Materials and Methods: The dataset for this research was derived from a comprehensive medical database, encompassing anonymised patient records of breast cancer and comorbidities. The study included adult patients of any gender with a confirmed diagnosis of breast cancer. Descriptive and inferential statistics were used for data analysis, employing Python libraries such as Pandas, NumPy, SciPy, Scikit-learn, Matplotlib, and Seaborn. The Chi-Square test and logistic regression analysis were applied to assess the association between diabetes and breast cancer stages while considering other comorbidities. Results: The study included 131 breast cancer patients, primarily females (98.47%), with a mean age of 54.2 years. About 22.14% had diabetes, and other comorbidities like dyslipidemia, hypertension, and hypothyroidism were also noted. The Chi-Square test revealed no significant association between diabetes and breast cancer stages (χ² = 3.07, p = 0.381). Logistic regression demonstrated limited effectiveness in predicting breast cancer stages, with varying accuracy across different stages. The most common stage diagnosed was Stage II, regardless of diabetes status. Conclusion: This study concludes that there is no significant association between diabetes and breast cancer stage among patients in the UAE after controlling for age and other comorbidities. The findings emphasise the importance of early breast cancer detection strategies that are not solely contingent on diabetes status. The study's limitations, such as its cross-sectional nature and small sample size, suggest the need for further research to understand the relationship between diabetes and breast cancer fully and to enhance breast cancer care in the UAE.